Kahramanmaraş İl Sınırları İçinde Tespit Edilen Türk Halk Müziği Eserlerinin İncelenmesi - Güvenç, Saadet (Sosyal Bilimler Enstitüsü, 1996)
Kahramanmaraş il sınırları içinde tespit edilen Türk Halk Müziği eserlerinin incelenmesi" konulu çalışma İstanbul Teknik Üniversitesi Enstitüsü Türk Halk Müziği Bölümü'nde bitirme tezi olarak hazırlanmıştır. "Kahramanmaraş Tarihi" coğrafya, şairlerine, gelenek ve göreneklerine yer verildikten sonra; kendi çalışmamız olan yöre ezgilerinin incelenmesine geçilmiştir. Bu ezgiler kendi aralarında incelenerek konular şimdiye kadar incelenmemiş olan nitelikleri ortaya çıkarılmıştır. Elde edilen sonuçlar doğrultusunda Kahramanmaraş halk müziğinin ince lenmesi konusunda bir çalışma oluşturulmuştur.

In this thesis we have tried to study sixteen folk melodies that belong to Kahramanmaraş, region in every aspects. In this study we have examined in detail Kahramanmaraş's history, its part Civilisation, geography, transportation, historical remains, proverbs, idioms, and the poets that have been born and lived in Kahramanmaraş and their works. The reason fort this is that we believe that the aforementioned, are the factors that influence music deeply. We thought that withoit examining them, we cannot analyse Kahramanmaraş Folk music thorougly. Therefore we have also examined them extremely careful. The main reason in choosing to examine the folk music of Kahramanmaraş region is that there have not been a thorough and detailed study in this area. Our procedure in this will beas such. a) Literary structure b) Chapters c) Sentences, that form a whole with small questions and answers. d) Small music sentences. -X - 1. HISTORY OF KAHRAMANMARAŞ The oldest name of Kahramanmaraş ant its history qoes back to the Asurs. The regions oldest name known to us is cited as Markasi. This name was also used during the Bzantium Period. The city named as "Maraş" during the Islamic period. Whan the city was reoccupied by Bysantium Empire, name of the city was changed as "Marasaion". After that, the Islamic period started again in this region and until the time 3 February 1 973 the name of the city ramained the same as "Maraş". On 3 February 1973 the name of the city changed as "Kahramanmaraş" due to then successful resistance movement in the city during the years national independence war. The history of region could be examined in seven periods. a- Hitit and Later Hitit period b- Roman Period c- Byzantium Period d- Selçuk Empire Period e- Prc-Ottoman Period f- Ottoman Empire Period g- The Republic Period -XI- The Historical Remains of Kahramanmaraş same of the remains are listed below: Kahramanmaraş castle, Ulu Mosque, Haznadar Mosque. Hatuniye Mosque. İklime Hatun Mosque. Ceyhan Bridge, Körsulu Bridge Kız Castle, Karahöyük, Taş Medrese. GEOGRAPHIC STRUCTURE OF KAHRAMANMARAŞ a) The situation of the city. Kahramanmaraş is on the east of Adana and Kayseri, on the west of Malatya and Gaziantep, on the south of Sivas and Adıyaman, and on the nort of Hatay. Its area is 14.327 km2, and the share of the city in total land of Turkey is 1.8 %. b) Its Landscape Mark. Its main mountains cund valley are es such: In The city is mainly located on south-east Toros mountains, 59.7 % of the city land is mountain aera. 24% of total land is platean. These are on the north of the city. Binboğa mountains, which is the branch of south-east Toros and surraunded the north of Afşin town, transforms to the platearus to the east. c) Climate The climate of the city has mixed charecteristic of Continental and Mediterranean Climates 3. The Culture of K. Maraş, a) In this thesis we, examined the idioms, provarios, phrases, oral puzzle, beliefs, customs and traditions of region. b) The Pets Of Kahramanmaraş We have conveyed the wandering minstrels and poets of Kahramanmaraş who are important for the regions history and culture with their life stories and exambles of their works. These poets are Hezari, Derdiçok, Af ş inli Aşık Yener. Aşık Meçhuli, Şazi, Berçenekli Aşık Mahsuni. c) Analysis of Music Sentences. Sentences are shown by capital letters and small sentencar are shown by small letters on the notes. d) The analysis of Rhytmic and melodic varionts. Melodic and Rhytmic variants in the melody are shown to throw ligh on the musical structure. 4. THE EXAMINATION PLAN IN THE FOLK SONES ANALYZED In this chapter there are the notes of the 1 6 lyrical folk melodies that have been examined. Each folk melody has been examined under the following five headings: Lyrical, Literary structure, rhythmical structure, melodic structure, and form structure. a) In this part lyrics, the sentence structure: ant uyal diagrams of the folk melodies are analyzed. The rhyme structure in the lines are shown a-b-c-d etc.... and the syllabic metres a b+5=1 1, 4+3=7, 4+4=8 etc. b) The Analysis of the Rhytmical structure of the türküs: In this part the rhythm, total measure number of the melody have been shown. c) The Anlysis of Melodic structures of the türküs: In this part cudanves, sound length, forte notes, altered notes, of the melodies have been shown in the whole. d) Analysis of Music Sentences. Sentences are shown by capital letters and small sentencer are shown by small letters on the notes. ~>CIII- e) The anlysis of Rhytmic and Melodic varionts. Melodic and Rhytmis variants in the melody are shown to throw ligh on the musical structure.
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 1996
Thesis (M.A.) -- İstanbul Technical University, Institute of Social Sciences, 1996
Keywords: Müzik; Halk müziği; Kahramanmaraş; Türk halk müziği; Music; Folk music; Kahramanmaraş; Turkish folk music